2017
DOI: 10.15666/aeer/1504_809827
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Drivers of Spatio-Temporal Land Use/Land Cover Changes in a Rapidly Urbanizing Area of China, the Su-Xi-Chang Region

Abstract: Abstract. The rapid economic development resulting from Chinese economic reform has greatly accelerated urbanization and industrialization, thus leading to alterations in the natural landscape. Understanding the extent of these changes is important for regional sustainable land management. An integrated approach with a geographic information system and remote sensing was used to extract land use/land cover (LULC) change information for the Su-Xi-Chang region over the period of 1980 to 2010. To calculate the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…These drivers are mainly originated from anthropogenic-induced activities (Harden 2014) even though natural factors, for instance, volcanic eruption, earthquake, landslide and climatological events also may contribute to substantial changes on planet earth. Anthropogenic-related drivers such as population growth (Geist et al 2006;Meshesha et al 2014), urbanization (d'Amour et al 2017Wang et al 2016;Yirsaw et al 2017), agricultural expansion (Ramankutty et al 2006;Mustard et al 2012), pasturing (Wassenaar et al 2007), and global market forces (Lambin & Meyfroidt 2011;Lambin et al 2003) are among the known drivers of LULCC. Besides such basic human-related drivers, recent studies indicated that climate change vulnerability has a significant forcing effect on LULCC (Biazin & Sterk 2013;Kindu et al 2015;Lambin et al 2003;Reid et al 2000;Zessner et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drivers are mainly originated from anthropogenic-induced activities (Harden 2014) even though natural factors, for instance, volcanic eruption, earthquake, landslide and climatological events also may contribute to substantial changes on planet earth. Anthropogenic-related drivers such as population growth (Geist et al 2006;Meshesha et al 2014), urbanization (d'Amour et al 2017Wang et al 2016;Yirsaw et al 2017), agricultural expansion (Ramankutty et al 2006;Mustard et al 2012), pasturing (Wassenaar et al 2007), and global market forces (Lambin & Meyfroidt 2011;Lambin et al 2003) are among the known drivers of LULCC. Besides such basic human-related drivers, recent studies indicated that climate change vulnerability has a significant forcing effect on LULCC (Biazin & Sterk 2013;Kindu et al 2015;Lambin et al 2003;Reid et al 2000;Zessner et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although LULCC drivers are recognized important globally, only a few studies integrated socioeconomic and climatic factors to investigate such change-cause relationships. In addition, LULCC drivers are markedly different in various time, landscape and region (Hassen & Assen 2018;Nzunda et al 2013;Yirsaw et al 2017). Hence, in regions like East Africa, where both LULCC and recurrent drought occurrence are the major environmental and livelihood challenges (Few et al 2015), consideration of climate variability as a potential driver of LULCC has a paramount importance in contributing to limited previous scientific literature in this region.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of urbanization, with the population agglomeration in cities and the continuous increase in urbanization level, cities must provide production and living facilities to satisfy the various needs of residents, and this is conducive to the expansion of the scale of nonagricultural land. Studies have demonstrated a significant positive relationship between population growth and urbanization level and urban construction land expansion [19,24]. The total population, urbanization rate, and other indicators are selected to quantify the effect of population and urbanization level on land use change [33].…”
Section: Influence Factors Of Land Use Transitionmentioning
confidence: 99%
“…Notably, in the process of rapid urbanization, the relationship between man and nature has been reshaped, and human production activities have greatly influenced land use transformation. Most studies have asserted that population growth, resident income, urbanization, industrialization, and other socioeconomic factors are the impetus for land use transformation [11,13,14,[19][20][21][22][23][24][25]. Additionally, the production activities of individuals were closely related to the institutional arrangements at a given time and place [11,[26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation